Nuovi modi di condividere il sapere (Milano University Press, 2023)
This second volume of the Unimi Connect – Universo Terza Missione series depicts a university that is opened up to society. The book provides a detailed account of 12 projects proving that knowledge can be a formidable engine of social innovation when it is shared with society.